Genetic variations in NADPH-CYP450 oxidoreductase in a Czech Slavic cohort - Tomková, Mária; Panda, Satya Prakash; Šeda, Ondřej; Baxová, Alice; Hůlková, Martina; Siler Masters, Bettie Sue; Martásek, Pavel (Pharmacogenomics, 2015)
AIM: Estimating polymorphic allele frequencies of the NADPH-CYP450 oxidoreductase (POR) gene in a Czech Slavic population. METHODS: The POR gene was analyzed in 322 individuals from a control cohort by sequencing and high resolution melting analysis. RESULTS: We identified seven unreported SNP genetic variations, including two SNPs in the 5' flanking region (g.4965C>T and g.4994G>T), one intronic variant (c.1899-20C>T), one synonymous SNP (p.20Ala=) and three nonsynonymous SNPs (p.Thr29Ser, p.Pro384Leu and p.Thr529Met). The p.Pro384Leu variant exhibited reduced enzymatic activities compared with wild-type. CONCLUSION: New POR variant identification indicates the number of uncommon variants might be specific for each subpopulation being investigated, particularly germane to the singular role that POR plays in providing reducing equivalents to all CYP450s in the endoplasmic reticulum. Original submitted 15 September 2014; Revision submitted 17 November 2014.
Keywords: kinetika; allele frequencies; Models, Molecular; systém (enzymů) cytochromů P-450; P450 reductase; jednonukleotidový polymorfismus; Male; DNA; Česká republika; Cohort Studies; Amino Acid Substitution; missense mutace; CYP; substituce aminokyselin; Haplotypes; mužské pohlaví; genetická variace; Adult; Mutation, Missense; Czech Republic; pharmacogenetics; kohortové studie; Cytochrome P-450 Enzyme System; NADPH-cytochrome; Linkage Disequilibrium; Genetic Variation; POR; Base Sequence; sekvence nukleotidů; Infant, Newborn; Protein Conformation; ženské pohlaví; novorozenec; molekulární modely; Humans; Czech Slavic population; vazebná nerovnováha; Kinetics; haplotypy; frekvence genu; P450 oxidoreductase; Gene Frequency; haplotype; dospělí; Female; lidé; konformace proteinů; Polymorphism, Single Nucleotide